Sistem Pendukung Keputusan Penerima Bantuan Beasiswa Miskin Dengan Metode AHP (Studi Kasus: Pertamina Plaju RU III) - Deka Ria Agustin; Ria Andryani (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
In this era, many applications are available in various online media such as the games such as Recipients of the Poor Scholarship Assistance (BSM) at Pertamina Plaju RU III Palembang have a disadvantage, namely using a manual selection process and subjective assessment. To solve this problem, a decision support system was established to determine recipients of poor scholarship assistance at Pertamina Plaju RU III Palembang using the Analytical Hierarchy Process (AHP) method. The criteria set by the selection team include: Family Card, Certificate of Disability from the RT, Letter of Parental Recitation (active card of ngaji dibazma), Transcript, Certificate of Not Receiving Scholarship from Campus, Electricity Account. This decision support system is supported by a method of decision making, namely the Analytical Hierarchy Process (AHP) method which is converted into a PHP programming language that can support data processing. Data modeling tools use Data Flow Diagrams (DFD), while design techniques use Entity Relationship Diagrams (ERD). The results of this study found that the system built can help the performance of the selection team determine students who are entitled to receive poor scholarship assistance